TINGKAT KEPUASAN PETANI KOPI TERHADAP KINERJA PENYULUH PERTANIAN DI KECAMATAN KALIPURO KABUPATEN BANYUWANGI - Kurnia, Daffa Varyno; Agustina, Titin (Jurnal Ekonomi Pertanian dan Agribisnis, 2024)
This research as a whole aims to (1) determine the level of farmer satisfaction with the performance of agricultural instructors in Kalipuro District, Banyuwangi Regency and (2) determine quality improvement strategies that can be carried out by agricultural instructors in Kalipuro District, Banyuwangi Regency. Determining the research location was carried out using a purposive method in Kalipuro District. The method used in this research is analytical descriptive. The data used in the research are primary data and secondary data. Sampling used purposive sampling and the results obtained were 60 farmer respondents with the criteria being that they were members of a farmer group, cultivated coffee and had received counseling, were farmer group administrators, and were willing to be interviewed. The data analysis methods in this research are descriptive analysis, Customer Satisfaction Index (CSI), and Important and Performance Analysis. The results of the research show (1) the level of farmer satisfaction with the performance of Agricultural Extension Workers in Kalipuro District, Banyuwangi Regency is 82.66%. This value is included in the range of 80%-100% so it can be stated that coffee farmers are very satisfied with the service performance of agricultural instructors in Kalipuro District (2) The strategy to improve the quality of service that can be implemented by agricultural instructors is to bridge cooperation between farmer groups and companies, both state and local. private sector in the form of partnerships to the use of e-commerce as a place for farmers to market their products.